Pengaruh Nilai Pelanggan Dan Electronic Word Of Mouth Terhadap Kepuasan Pengunjung Dengan Keputusan Berkunjung Sebagai Variabel Intervening Pada New Marjoly Beach And Resort - Atika Rosifa; Lia Suprihartini; Roni Kurniawan (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
This study aims to determine the effect of customer value on visitor satisfaction through visiting decisions, the influence of electronic word of mouth on visitor satisfaction through visiting decisions, the effect of customer value and electronic word of mouth partially on visiting decisions, the influence of customer value and electronic word of mouth partial to visitor satisfaction and the effect of visiting decisions on visitor satisfaction. Determination of the sample using the incidental sampling method, with the sampling technique using the Slovin formula to obtain 96 respondents. The analysis method used in this research is descriptive test, data quality test, classic assumption test, path analysis, and hypothesis testing. The results of the analysis in this study indicate that customer value partially has a significant effect on visitor satisfaction. Partially, electronic word of mouth has a significant effect on visitor satisfaction. Customer value partially has a significant effect on visiting decisions. Partially, electronic word of mouth has no significant effect on visiting decisions. The decision to visit is not able to mediate between customer value and visitor satisfaction and the decision to visit is also unable to mediate between electronic word of mouth and visitor satisfaction. Based on the research results, it is hoped that the new marjoly beach and resort can maintain and increase visitor satisfaction by paying attention to what factors can support customer value and electronic word of mouth.